Manufactured of "Mestura cocida" from Celta pig breed. Study of shelf life vacuum packaging - Lorenzo J.M.; García-Fontán M.C.; Purriños L.; Valledor P.; Franco D. (7th International Symposium on the Mediterranean Pig, 2012)
"Mestura cocida" is a typical product manufacture and consumed in Galicia (NW Spain) elaborated with dry-cured "lacón", "Galician chorizo" and salted head from Celta pig breed. The elaboration process is strictly controlled to achieve a satisfactory shelf life, so a high quality finally-consumed product is obtained. Physical, chemical, enzymic and microbiological test are performed to ensure this quality. Psychrotrophs, Enterobacteriaceae, Staphylococcus aureus, Salmonella, sulfite reducing clostridia and TBAR´S value were analysed during storage at 4°C. Psychrotrophs and Enterobacteriaceae showed a increase during storage observed final values 7.88 and 5.12 log cfu/g, respectively after 90 days of storage. Staphylococcus aureus and Salmonella have not been found in any samples. On the other hand, TBAR´S values increased) during the whole display period reaching a final values of 11.8 mg malonaldehyde / kg of "Mestura cocida".
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)